Progesterone Receptor-Mediated Regulation of N-Acetylneuraminate Pyruvate Lyase (NPL) in Mouse Uterine Luminal Epithelium and Nonessential Role of NPL in Uterine Function - Xiao, Shuo; Li, Rong; Diao, Honglu; Zhao, Fei; Ye, Xiaoqin (PLOS ONE, 2013)
N-acetylneuraminate pyruvate lyase (NPL) catalyzes N-acetylneuraminic acid, the predominant sialic acid. Microarray analysis of the periimplantation mouse uterine luminal epithelium (LE) revealed Npl being the most downregulated (35×) gene in the LE upon embryo implantation. In natural pregnant mouse uterus, Npl expression increased 56× from gestation day 0.5 (D0.5) to D2.5. In ovariectomized mouse uterus, Npl was significantly upregulated by progesterone (P4) but downregulated by 17β-estradiol (E2). Progesterone receptor (PR) antagonist RU486 blocked the upregulation of Npl in both preimplantation uterus and P4-treated ovariectomized uterus. Npl was specifically localized in the preimplantation D2.5 and D3.5 uterine LE. Since LE is essential for establishing uterine receptivity, it was hypothesized that NPL might play a critical role in uterine function, especially during embryo implantation. This hypothesis was tested in the Npl(−/−) mice. No significant differences were observed in the numbers of implantation sites on D4.5, gestation periods, litter sizes, and postnatal offspring growth between wild type (WT) and Npl(−/−) females from mating with WT males. Npl(−/−)xNpl(−/−) crosses produced comparable little sizes as that from WTxWT crosses. Comparable mRNA expression levels of several genes involved in sialic acid metabolism were observed in D3.5 uterus and uterine LE between WT and Npl(−/−), indicating no compensatory upregulation in the D3.5 Npl(−/−) uterus and LE. This study demonstrates PR-mediated dynamic expression of Npl in the periimplantation uterus and dispensable role of Npl in uterine function and embryo development.